2016
DOI: 10.1080/15592324.2016.1152438
|View full text |Cite
|
Sign up to set email alerts
|

GIPC: Glycosyl Inositol Phospho Ceramides, the major sphingolipids on earth

Abstract: What are the most abundant sphingolipids on earth? The answer is Glycosyl Inositol Phosphoryl Ceramides (GIPCs) present in fungi and the green lineage. In this review, we discuss the putative role of plant GIPCs in the lipid bilayer asymmetry, in the lateral organization of membrane rafts and in the very long chain fatty acid inter-leaflet coupling of lipids in the plant plasma membrane (PM). A special focus on the structural similarities -and putative functions-of GIPCs is discussed by comparison with animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 35 publications
(48 reference statements)
1
67
0
Order By: Relevance
“…Sphingolipids and their glycosylated forms together with plant sterols are important constituents of the lipid rafts of the plasma membrane (Msanne et al, 2015). The complex GCIPC are considered as the equivalents of complex glycosphingolipids like gangliosides in animal cells (Gronnier et al, 2016;Cacas et al, 2016). They play important roles in regulation of cellular processes, such as cell wall formation, programmed cell death, drought and salt tolerance (Ali et al, 2018).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…Sphingolipids and their glycosylated forms together with plant sterols are important constituents of the lipid rafts of the plasma membrane (Msanne et al, 2015). The complex GCIPC are considered as the equivalents of complex glycosphingolipids like gangliosides in animal cells (Gronnier et al, 2016;Cacas et al, 2016). They play important roles in regulation of cellular processes, such as cell wall formation, programmed cell death, drought and salt tolerance (Ali et al, 2018).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…It was shown that GIPCs are capable of binding rhamnogalacturonan II, which is a fraction of pectin [25]. GIPCs are lipids with very long saturated acyl chains organized in membrane domains at the plasma membrane [26]. It was calculated that the carbon atom acyl chains of GIPC are too long to fit in one leaflet and will therefor penetrate within the inner leaflet and interdigitate with the inner leaflet lipid acyl chains [26].…”
Section: The Plasma Membrane-a Sensor Of the Mechanical State Of The mentioning
confidence: 99%
“…GIPCs are lipids with very long saturated acyl chains organized in membrane domains at the plasma membrane [26]. It was calculated that the carbon atom acyl chains of GIPC are too long to fit in one leaflet and will therefor penetrate within the inner leaflet and interdigitate with the inner leaflet lipid acyl chains [26]. This makes GIPCs putative links between the plasma membrane and the cell wall, which could access the plasma membrane to recognize the current physical state of the cell.…”
Section: The Plasma Membrane-a Sensor Of the Mechanical State Of The mentioning
confidence: 99%
“…The sphingolipidome of plants contains glycosyl inositol phospho ceramides (GIPCs), glycosylceramides and ceramides, whereas sphingomyelin, globosides, sulfatides or gangliosides are absent. GIPCs were characterized as the major sphingolipid on earth due to their high abundance in plants and fungi, which comprise a large portion of the biomass of the biosphere [ 1 ]. GIPCs were first described more than 60 years ago as “phytoglycolipids” [ 2 ].…”
Section: Introductionmentioning
confidence: 99%